2012
DOI: 10.1111/boc.201200014
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signature in various cell types of mouse spermatogenesis: Evidence for stage‐specifically expressed miRNA‐221, ‐203 and ‐34b‐5p mediated spermatogenesis regulation

Abstract: Taken together, we established the miRNA signature of SSC, PrM and meiotic cells and show evidence for their functional relevance during the process of spermatogenesis by target prediction and validation. Through our observations, we propose a working model in which the stage-specific miRNAs such as miR-221, -203 and -34b-5p coordinate the regulation of spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 54 publications
3
71
1
1
Order By: Relevance
“…ly, miR-34b-5p and miR-449a, which are members of the miR-34/449 family, have been reported to be preferentially expressed in the testis, especially in meiotic cells during spermatogenesis in mice (Smorag et al, 2012). Therefore, the down-regulation of miR-34b-5p and miR-449a might reflect the depletion of meiotic cells such as pachytene spermatocytes in EGME-treated monkeys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ly, miR-34b-5p and miR-449a, which are members of the miR-34/449 family, have been reported to be preferentially expressed in the testis, especially in meiotic cells during spermatogenesis in mice (Smorag et al, 2012). Therefore, the down-regulation of miR-34b-5p and miR-449a might reflect the depletion of meiotic cells such as pachytene spermatocytes in EGME-treated monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The target miRNAs, miR-34b-5p and miR-449a in the testis, which were associated with spermatogenesis or EGME induced-testicular toxicity (Fukushima et al, 2011;Lizé et al, 2011;Smorag et al, 2012;Wu et al, 2014), were applied to RT-qPCR with 7900HT Fast Real Time PCR System (Applied Biosystems). The primers for miR-34b-5p and miR-449a (Assay IDs: #000427 and 001030) were designed based on each respective human sequence obtained from miRBase (http://microrna.sanger.…”
Section: Reverse Transcription-quantitative Real-time Pcr (Rt-qpcr) Amentioning
confidence: 99%
“…Interestingly, miR-34c has also been shown to promote murine male germ cell apoptosis by targeting the transcription factor ATF1 in a p53-independent manner [122]. In mouse models, miR-34c and miR-34b were found to be highly expressed in post-mitotic male germ cells from primary spermatocytes up to round spermatids [121,123], and deletion of this locus along with miR-449 led to OAT and infertility [124]. Remarkably, miR-34c seems to extend its reproductive role into the zygote, as sperm-borne miR-34c has been shown to Patients with oligoospermia / oligoasthenozoospermia (80) and NOA (40) Spermatozoa and testicular tissues miR-429 was significantly increased, whereas miR-34b*, miR-34b, miR-34c-5p…”
Section: Spermatozoal Mirnas and Male Infertilitymentioning
confidence: 99%
“…For instance, it has been reported that all spermatogonia isolated from 8-day-old mice display detectable KIT mRNA, but 30-50% of these lack protein expression (Prabhu et al, 2006), presumably implying cell specific translational control mechanisms exerted by microRNA and/ or RNA-binding proteins, which are known to play fundamental roles in the regulation of spermatogenesis Messina et al, 2012). Very recently miRNA 221, which was previously known to target Kit mRNA in hematopoietic stem cells, has been shown to be specifically expressed in spermatogonial stem cells (Smorag et al, 2012), and evidence has been given that both KIT mRNA and KIT protein abundance are influenced by miRNA 221 and miRNA 222 function in spermatogonia (Yang et al, 2013). These results imply that, together with repression of Kit transcription exerted by PLZF, microRNAs actually contribute to post-transcriptional silencing of Kit expression in the spermatogonial stem cell pool.…”
Section: Transcription Factors Controlling Kit Expression In the Germmentioning
confidence: 99%